Design and Conduct Considerations for First‐in‐Human Trials. Issue 1 (24th August 2018) - Shen, Jie; Swift, Brandon; Mamelok, Richard; Pine, Samuel; Sinclair, John; Attar, Mayssa
Abstract : A milestone step in translational science to transform basic scientific discoveries into therapeutic applications is the advancement of a drug candidate from preclinical studies to initial human testing. First‐in‐human (FIH) trials serve as the link to advance new promising drug candidates and are conducted primarily to determine the safe dose range for further clinical development. Cross‐functional collaboration is essential to ensure efficient and successful FIH trials. The aim of this publication is to serve as a tutorial for conducting FIH trials for both small molecule and biological drug candidates with topics covering regulatory requirements, preclinical safety testing, study design considerations, safety monitoring, biomarker assessment, and global considerations. An emphasis is placed on FIH trial design considerations, including starting dose selection, study size and population, dose escalation scheme, and implementation of adaptive designs. In light of the recent revision of the European Medicines Agency (EMA) guideline on FIH trials to promote safety and mitigate risk, we also discuss new measures introduced in the guideline that impact FIH trial design.